(3LGeY GdJMUjd aj CMcGe GdeQGSjds - (3UdGM GdOjf GdYdGFj , UdGM GdOjf CHh SYjO,J (B761 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf Gddg SHMGfg aVd gPg GdGFeI HTQa GdGSfGO hSejJg LGeY GdJaUjd dCMcGe GdeQGSjd hQJHJg Ydi SJI GHhGH s
(3BNQgG (B:s
(3MOjK Hf GdeSjH fhMOg cdg eSfO eJUdkG aEcJai Yf WdH cd MOjK s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B321 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B126s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B538s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3CUhd Gdabgs